Improving Student Learning Outcomes in Mathematics Learning Using Interactive Powerpoint at MI Negeri 2 Ambon - Heriani, Vivi (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve student learning outcomes in Islamic religious education learning by using interactive powerpoint. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that interactive powerpoint can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 48.71%, the first cycle 63.39% and in the second cycle it increased to 90.96%. Thus, the use of interactive powerpoint can be used as an alternative to improve student learning outcomes in Islamic religious education learning.